2020
DOI: 10.1016/j.nicl.2019.102123
|View full text |Cite
|
Sign up to set email alerts
|

Altered frontal white matter microstructure is associated with working memory impairments in adolescents with congenital heart disease: A diffusion tensor imaging study

Abstract: HighlightsPatients with congenital heart disease (CHD) are at risk for lower working memory.CHD patients showed widespread alterations in white matter microstructure using DTI.Alterations in frontal white matter were associated with working memory problems.This association was independent of CHD type, IQ and group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…Furthermore, various studies have shown that alterations of white matter microstructure are still present in adolescents with CHD: In adolescents with repaired transposition of the great arteries, FA was significantly lower compared to controls in the bilateral deep white matter, cerebral cortex, cerebellum and mid-brain ( Rivkin et al , 2013 ) and white matter network topology was altered ( Panigrahy et al , 2015 ). Tract-based spatial statistics analyses in two cohorts of Fontan patients ( Watson et al , 2018 ) and patients with different types of cyanotic and acyanotic CHD ( Ehrler et al , 2020 ) have revealed widely overlapping reduced FA in almost every cortical and sub-cortical white matter tract. From studies in emerging adults, there is evidence that alterations in the white matter may persist into adulthood ( Brewster et al , 2015 ; Easson et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, various studies have shown that alterations of white matter microstructure are still present in adolescents with CHD: In adolescents with repaired transposition of the great arteries, FA was significantly lower compared to controls in the bilateral deep white matter, cerebral cortex, cerebellum and mid-brain ( Rivkin et al , 2013 ) and white matter network topology was altered ( Panigrahy et al , 2015 ). Tract-based spatial statistics analyses in two cohorts of Fontan patients ( Watson et al , 2018 ) and patients with different types of cyanotic and acyanotic CHD ( Ehrler et al , 2020 ) have revealed widely overlapping reduced FA in almost every cortical and sub-cortical white matter tract. From studies in emerging adults, there is evidence that alterations in the white matter may persist into adulthood ( Brewster et al , 2015 ; Easson et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Birca and colleagues (2016) has shown that microstructural alterations are associated with reduced functional connectivity measured with EEG. Studies in adolescents with CHD have further demonstrated associations between reduced local white matter anisotropy and cognitive impairments in domains such as working memory ( Ehrler et al , 2020 ), intelligence ( Watson et al , 2018 ), executive function and behaviour ( Rollins et al , 2014 ), attention and learning ( Brewster et al , 2015 ). In light of the large extent of persisting alterations in projection, commissural and association tracts connecting various brain regions, the associated impact of these structural changes on different aspects of neurodevelopmental (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced WM axonal packing could impair communication between different brain regions [ 86 ]. The degree of global WM network topology disturbances correlates with overall neurocognitive performance, WMI in the uncinate fasciculus correlates with verbal memory impairments, WMI in the frontal lobe associates with working memory deficits, and WMI of the middle cerebellar peduncle correlates with auditory attention span [ 30 , 31 , 87 ].…”
Section: Factors That Predict Neurological Injury and Neurodevelopmenmentioning
confidence: 99%
“…By adolescence, the neurodevelopmental delay persisted and manifested as impairments of neuromotor, intellectual, executive function, visuomotor, perception and integration skills. Lasting cerebral WMI and microstructural alterations, cerebellar white matter and cerebellar volume loss contributed to the neurodevelopmental deficits [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%